THE INFLUENCE OF TECHNOLOGY ON THE INCOME OF MICRO FASHION ENTERPRISES IN DENPASAR CITY - Ni Luh Putu Yeni Laksmini Putri; Ida Ayu Meisthya Pratiwi (Adisam Publisher, 2025)
Micro-enterprises, particularly in the fashion sector, play a strategic role in promoting local economic growth in Denpasar City. However, optimizing income remains a challenge due to constraints in capital, technology utilization, and labor. This study aims to analyze the influence of e-commerce, financial technology, social media, business capital, and labor quantity on the income of micro fashion enterprises. Using an associative quantitative approach, data were collected from 99 respondents through observation, interviews, and questionnaires, and analyzed using multiple linear regression. The results show that all variables simultaneously have a significant effect on income. Partially, e-commerce, financial technology, and social media have a significantly positive impact on income growth. In contrast, business capital and labor do not show a significant effect due to the nature of micro fashion enterprises, which tend to focus on selling finished products and leveraging digital tools, thus requiring neither large capital nor a substantial workforce. These findings highlight the crucial role of digital transformation as a key driver of success for micro fashion businesses in the digital economy era.